N-Acetylglucosamine Kinase, HXK1 Is Involved in Morphogenetic Transition and Metabolic Gene Expression in Candida albicans - Rao, Kongara Hanumantha (Public Library of Science, 2013)

(untitled)
Candida albicans, a common fungal pathogen which diverged from the baker’s yeast Saccharomyces cerevisiae has the unique ability to utilise N-acetylglucosamine, an amino sugar and exhibits phenotypic differences. It has acquired intricate regulatory mechanisms at different levels in accordance with its life style. N-acetylglucosamine kinase, a component of the N-acetylglucosamine catabolic cascade is an understudied gene since Saccharomyces cerevisiae lacks it. We report HXK1 to act as both positive and negative regulator of transcription of genes involved in maintaining cellular homeostasis. It is involved in repression of hyphal specific genes in addition to metabolic genes. Its regulation of filamentation and GlcNAc metabolism is independent of the known classical regulators like EFG1, CPH1, RAS1, TPK2 or TUP1. Moreover, Hxk1-GFP is localised to cytoplasm, nucleus and mitochondria in a condition specific manner. By employing two-step affinity purification, we report the interaction of HXK1 with SIR2 under filamentation inducing conditions. Our work highlights a novel regulatory mechanism involved in filamentation repression and attempts to decipher the GlcNAc catabolic regulatory cascade in eukaryotes.